Customer capital and trade intermediaries: Evidence from China - Lee, Jungho (Institutional Knowledge at Singapore Management University, 2023)
Using a unique dataset that links the production and sales of Chinese exporting firms, we document that the value of export goods a firm produces often differs from the value of export goods that the firm sells in foreign markets. We show that this empirical pattern reflects that some exporters act as trade intermediaries, which we refer to as producer intermediaries. We further show that firms with higher accumulated marketing expenditures are more likely to become producer intermediaries. To understand the implications of our empirical findings, we develop a theoretical framework in which firms can lend and borrow customer capital through outsourcing. Firms with high foreign-customer capital can facilitate trade by outsourcing their export demand to productive firms with limited customer capital, even when frictions prevent optimal outsourcing. Our estimated model indicates that gains from outsourcing can be substantial, with producer intermediaries generating a large portion of these gains.